A Common Suite of Coagulation Proteins Function in Drosophila Muscle Attachment. Issue 3 (1st November 2016) - Green, Nicole; Odell, Nadia; Zych, Molly; Clark, Cheryl; Wang, Zong-Heng; Biersmith, Bridget; Bajzek, Clara; Cook, Kevin R; Dushay, Mitchell S; Geisbrecht, Erika R
Abstract: The organization and stability of higher order structures that form in the extracellular matrix (ECM) to mediate the attachment of muscles are poorly understood. We have made the surprising discovery that a subset of clotting factor proteins are also essential for muscle attachment in the model organism Drosophila melanogaster . One such coagulation protein, Fondue (Fon), was identified as a novel muscle mutant in a pupal lethal genetic screen. Fon accumulates at muscle attachment sites and removal of this protein results in decreased locomotor behavior and detached larval muscles. A sensitized genetic background assay reveals that fon functions with the known muscle attachment genes Thrombospondin ( Tsp ) and Tiggrin (Tig ). Interestingly, Tig is also a component of the hemolymph clot. We further demonstrate that an additional clotting protein, Larval serum protein 1γ (Lsp1γ), is also required for muscle attachment stability and accumulates where muscles attach to tendons. While the local biomechanical and organizational properties of the ECM vary greatly depending on the tissue microenvironment, we propose that shared extracellular protein–protein interactions influence the strength and elasticity of ECM proteins in both coagulation and muscle attachment.